La voluntad política en el discurso anticorrupción: ¿parteaguas o mecanismo de lucha selectiva? El caso de México (2018-2024) - Arellano Gault, David; Rojas Salazar, Gabriel (El Colegio de México A.C., 2025)
This article analyzes the anti-corruption discourse of Andrés Manuel López Obrador’s administration (2018–2024), focusing on the notion of “political will” as its guiding principle. It examines how this concept, frequently used in the anti-corruption literature as a critical variable, lacks clear operationalization. In practice, its use tends to be generic and rhetorical, allowing for the justification of selective anti-corruption efforts. Through an analysis of the Segalmex case—an alleged corruption scandal—the study evaluates whether government initiatives employed the concept of political will in this way. The findings suggest that the anti-corruption policy prioritized rhetoric, and the symbolism associated with political will, fostering a selective approach. In particular, the study observes that a strongly moralistic discourse tended to downplay irregularities committed by government officials. The conclusion is that the rhetoric of political will, when lacking clear definitions and commitments, paradoxically facilitates the justification and concealment of systemic dynamics of illegality, fraud, and embezzlement.